Exploring the Impact of Brand Attributes on Tourism Revisit Intentions: The Mediating Effects of Perceived Value, Brand Awareness, and Brand Loyalty in Phuket, Thailand - Intuluck, Watit; Tadawattanawit, Surakiat; Srisakun, Chakrit; Rattanataworn, Phopdech (Thammasat Review, 2024)
This study investigates the mediating roles of perceived value, brand awareness, and brand loyalty in the relationship between brand attributes and tourism revisit intentions among high-quality tourists in Phuket, Thailand. Drawing on a robust theoretical framework, the study employs Process Macro methodology to analyze data collected from 254 domestic tourists, using a 5-point Likert scale questionnaire. The findings confirm that brand attributes have a significant positive impact on perceived value, brand awareness, brand loyalty, and tourism revisit intentions. Additionally, the study demonstrates that perceived value, brand awareness, and brand loyalty serve as crucial mediators, enhancing the influence of brand attributes on revisit intentions. These results align with existing literature, reinforcing the importance of strong brand attributes in shaping tourists’ perceptions and behaviors. The study provides valuable theoretical contributions by extending the application of brand management theories to the tourism context and offers practical insights for destination marketers in designing effective branding strategies to foster tourist loyalty and encourage repeat visits. Despite the study’s focus on Phuket, the findings suggest broader implications for tourism destinations in Thailand, and future research is recommended to explore these relationships across different regions and tourist segments.